Looking to the future of quantum optics. - Walmsley, I (2008)
Light has provided both fundamental phenomenology and enabling technology for scientific discovery for many years, and today it continues to play a central role in fundamental explorations and innovative applications. The ability to manipulate light beams and pulses with the quantum degrees of freedom of optical radiation will add to those advances. The future of quantum optics, which encompasses both the generation and manipulation of nonclassical radiation, as well as its interaction with matter, lies in the rich variety of quantum states that is now becoming feasible to prepare, together with the numerous applications in sensing, imaging, metrology, communications, and information processing that such states enable.